Immune mediators as plasma biomarkers for identifying household contacts and classifying clinical forms and leprosy reactions - Carvalho, Jairo Campos; Pascoal-Xavier, Marcelo Antônio; Araújo, Marcelo Grossi; Martins, Júlia Pereira; Teixeira-Carvalho, Andrea; Gomes, Matheus de Souza; Amaral, Laurence Rodrigues; Peruhype-Magalhães, Vanessa; Coelho-dos-Reis, Jordana Grazziela Alves; Martins-Filho, Olindo Assis; Araújo, Márcio Sobreira Silva (Frontiers in Immunology, 2025)
The present study aimed to evaluate the performance of plasma immune mediators in classifying leprosy patients [L(PB) and L(MB), paucibacillary and multibacillary leprosy, respectively], leprosy reaction patients (T1LR and T2LR, type 1 and type 2 leprosy reaction, respectively), household contacts (HHC), and non-infected (NI) controls. Quantitative measurements of these immune mediators were carried out using high-throughput multiplex microbead array. The results demonstrated that most of the plasma immune mediators were increased in all clinical groups compared with NI controls. Higher frequencies but lower maximum magnitudes of increase (fold change according to NI) were observed for T1LR (63%, 6.1×) and T2LR (63%, 9.7×) compared with HHC (48%, 68.5×), L(PB) (56%, 8.5×), and L(MB) (48%, 37.9×). The bi-dimensional scattering profiles (magnitude order vs. significance) identified a higher number of immune mediators in T2LR (12/27) compared with HHC (8/27), L(PB) (7/27), L(MB) (5/27), and T1LR (5/27). CXCL8 was selected as the parameter with the highest accuracy and significance [area under the receiver operating characteristic curve (AUC) = 0.98, p = 0.0002] in classifying NI vs. HHC. CCL3 (C–C motif chemokine ligand 3) was the single analyte with moderate accuracy and significance (AUC = 0.74, p = 0.0422) in classifying L(PB) vs. L(MB). IL-9 was selected as an attribute with moderate accuracy and significance (AUC = 0.77, p = 0.0041) in classifying T1LR vs. T2LR. Decision tree algorithms confirmed the high accuracy (96%) of CXCL8 in classifying NI vs. HHC. The use of CCL3 followed by IFN-γ classified L(MB) vs. L(PB) with high accuracy (93%). Moreover, the analysis of IL-9 followed by IL-6 and CXCL10 classified T1RL vs. T2RL with high accuracy (96%). In general, combined stepwise algorithms showed enhanced classification accuracy compared with single-attribute analysis. Together, our findings supported the potential use of plasma immune mediators as complementary laboratory biomarkers for the identification of HHC and the classification of distinct clinical forms of leprosy and leprosy reactions.